Immunoglobulin Classes and Biological Functions of Campylobacter (Vibrio) fetus Antibodies in Serum and Cervicovaginal Mucus - Corbeil, L. B. (1974)
Serum and cervicovaginal mucus (CVM) antibodies from heifers after genital infection or systemic immunization with Campylobacter (Vibrio) fetus were classified according to their immunoglobulin class, antigenic specificities, and biological functions. Only immunoglobulin (Ig) A antibodies, specific both for O and superficial, heat-labile, whole-cell (W) antigens, were detected in CVM of convalescent animals. After systemic immunization, antibodies in serum were directed principally to W antigens and were located in IgG(1), IgG(2), and IgM classes; CVM antibodies of the same specificity were detected only in the IgG subclasses. Functional tests revealed that antibodies of W specificity, whether of the IgA or IgG class, were capable of immobilizing the organism. However, IgG antibodies immobilized with clumping, whereas IgA antibodies immobilized single organisms within the 3-min period. None of the antibody preparations was bactericidal in the presence of homologous complement when the infecting strain was used as the target organism, but a bactericidal effect was observed when the target strain was rough and non-encapsulated. Both serum and CVM from systemically immunized animals opsonized C. fetus organisms, but CVM from locally immunized animals containing IgA antibodies was not opsonic. It is hypothesized that functions of immobilization for IgA and IgG and of opsonization for IgG are important features of protective immunity in venereal vibriosis.